Somatic determinants of the sport performance of Polish sprinters - Ozimek, M.; Nowak, M.; Krawczyk, M.; Zaborova, V.; Herbert, J.; Cepicka, L.; Mirek, W. (Journal of Kinesiology and Exercise Sciences, 2021)
Aim. The aim of this study was to identify the determinants of somatic build of athletes at different (national and club) levels of sports skills. Furthermore, the study attempted to establish relationships between the performance in the 100m and 200m sprints and the parameters studied in the groups of sprinters and a control group (university students). Materials. The study included a selected group of sprinters (n=34). The sports skill level of the athletes was determined according to the track and field standards of the Polish Athletics Association (Polish: Polski Zwiazek Lekkiej Atletyki, PZLA) as a sports class (Class I: national level, Class II: club level). The control group (n=62) consisted of sophomore full-time male students of physical education from the University of Physical Education in Krakow, Poland. Results and Conclusions. The results indicated that there was little intergroup variation in somatic build for characteristics such as hip width, elbow width, arm circumference, and largest thigh circumference. A significant effect on the improvement in scores in Class I athletes was found for R skinfold (over ticeps skin-fold) in 100m sprinters and the sum of R+L skinfolds (over ticeps + subscapular skin-fold) in 200m sprinters. In other groups, associations with the 100m score were shown for shoulder width, lower limb length, B skinfold (on abdonmen skin-fold), L skinfold, R skinfold, hip width, whereas for 200m, this concerned the largest lower leg circumference and R skinfold.